MARGIN APRESIASI HARMONISASI HUKUM INDONESIA DALAM PERSPEKTIF EMPAT PILAR ASEAN ECONOMIC COMMUNITY1 - Ridwan Ridwan (UNIB Press, 2015)
ABSTRACTThe implementation of the AEC in 2015 will make ASEAN transformedin to pillars as a single market and production base, a highly competitive economic region, the region with equitable e conomic development and a region fully integrated into the global economy. The implentation of the AEC will also transform the Indonesian law that is necessary to change the law as a juridical instrument to implement the AEC. How to appreciate the AEC and legal change show it should be done? Appreciation and legal changes cannot be separated from the other pillars of the ASEAN Community, namely the security community and socio-cultural community. Thus, as the margin of appreciationis none other than the Pancasila and Indonesian state goals, as well as changes in the meaning of the law is the law harmonization. Thus implementation in the context of the AEC should utilize AEC aspirations for national interests, while protecting the interests of the peoples, as well as aligning with the AEC between national interests and global. Keywords: AEC, Transforms, Appreciation, Pancasila, the Stategoals, Harmonization.ABSTRAKImplementasikan AEC tahun 2015 akan mentansformasi ASEAN ke dalam pilar-pilar sebagai pasar tunggal dan basis produksi, kawasan ekonomi yang berdaya saing tinggi, kawasan dengan pembangunan ekonomi yang merata, dan kawasan yang terintegrasi ke dalam ekonomi global. Implementasi AEC juga akan mentranformasi hukum Indonesia sehingga perlu dilakukan perubahan hukum sebagai instrumen yuridis untuk mengimplementasikan AEC tersebut. Bagaimana mengapresiasi AEC dan perubahan hukum yang bagaimana harus dilakukan? Apresiasi dan perubahan hukum tidak terlepas dari pilar komunitas ASEAN yang lain yaitu komunitas keamanan dan komunitas sosial budaya. Dengan demikian, sebagai margin apresiasi tidak lain adalah Pancasila dan tujuan negara Indonesia, serta perubahan hukum adalah dalam arti harmonisasi hukum. Dengan demikian implementasi AEC harus dalam konteks yaitu memanfaatkan aspirasi AEC bagi kepentingan nasional, sekaligus menganyomi kepentingan rakyat, serta menyelaraskan antar kepentingan nasional dengan AEC dan global.Kata Kunci: AEC, Mentransformasi, Apresiasi, Pancasila, Tujuan Negara, Harmonisasi.